(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Fiber Bragg Grating (FBG) is a crucial optical waveguide device widely used in sensing, filtering, and optical communication. In recent years, High Birefringence Photonic Crystal Fiber (HB-PCF) has emerged as an important optical transmission medium in complex optical environments due to its outstanding polarization-maintaining capability and structural design flexibility. This paper investigates the spectral characteristics of uniform FBGs embedded in HB-PCF through theoretical modeling and coupled-mode analysis, systematically examining the dual reflection peaks phenomenon, polarization-dependent spectral response, mode-selective reflection behavior, bandwidth and reflectivity properties, as well as dispersion characteristics. The results demonstrate that the HB-PCF-FBG structure exhibits significant advantages for polarization-sensitive applications, high-precision sensing, and dispersion control, highlighting its excellent potential for engineering applications.